Autoantibodies to calpastatin (an endogenous inhibitor for calcium-dependent neutral protease, calpain) in systemic rheumatic diseases. - Mimori, T (1995)
We identified an autoantibody that reacts with calpastatin [an inhibitor protein of the calcium-dependent neutral protease calpain (EC 3.4.22.17)]. In early immunoblot studies, sera from patients with rheumatoid arthritis (RA) recognized unidentified 60-, 45-, and 75-kDa proteins in HeLa cell extracts. To identify these autoantigens, we used patient sera to clone cDNAs from a lambda gt11 expression library. We isolated clones of four genes that expressed fusion proteins recognized by RA sera. The 1.2-kb cDNA insert (termed RA-6) appeared to encode a polypeptide corresponding to the 60-kDa antigen from HeLa cells, since antibodies bound to the RA-6 fusion protein also reacted with a 60-kDa HeLa protein. The deduced amino acid sequence of the RA-6 cDNA was completely identical with the C-terminal 178 amino acids of human calpastatin except for one amino acid substitution. Patient sera that reacted with the RA-6 also bound pig muscle calpastatin, and a monoclonal antibody to human calpastatin recognized the RA-6 fusion protein, confirming the identity of RA-6 with calpastatin. Moreover, the purified RA-6 fusion protein inhibited the proteolytic activity of calpain, and IgG from a serum containing anti-calpastatin antibodies blocked the calpastatin activity of the RA-6 fusion protein. Immunoblots of the RA-6 product detected autoantibodies to calpastatin in 57% of RA patients; this incidence was significantly higher than that observed in other systemic rheumatic diseases, including systemic lupus erythematosus (27%), polymyositis/dermatomyositis (24%), systemic sclerosis (38%), and overlap syndrome (29%). Thus, anti-calpastatin antibodies are present most frequently in patients with RA and may participate in pathogenic mechanisms of rheumatic diseases.